Pengaruh Kompetensi, Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Kantor Bank Kalsel Cabang Pembantu di Banjarmasin - Rozi Fadillah; Sulastini Sulastini; Noor Hidayati (JURNAL BISNIS DAN PEMBANGUNAN, 2017)
The purpose of this study to prove the influence of Competence (X1), Work Discipline (X2), and the Working Environment (X3) on employee performance (Y)Location Research Office Bank Branch in Banjarmasin city in South Kalimantan, that concist from 4 office branch with the size a sample of 48 employees were selected by sampling saturated. Collecting data using questionnaires designed using level Likert scale 1-5. Data analysis using PLS.The test results prove competency significantly influence employee performance Bank branch Banjarmasin in South Kalimantan, with great effect by 66%, Work Discipline not significant effect on Employee Performance Bank branch in South Kalimantan Banjarmasin with great effect by 6.6%, and the Working Environment effect is not significant the Employee performance Bank branch in South Kalimantan Banjarmasin with great influence with the great influence of 11%. Keywords: Competence, Work Discipline and Work Environment and Employee Performance